The biomechanical study of a modified lumbar interbody fusion—crenel lateral interbody fusion (CLIF): a three-dimensional finite-element analysis. Issue 9 (3rd July 2020) - Chen, Yun-lin; Lai, Ou-jie; Wang, Yang; Ma, Wei-hu; Chen, Qi-xin
Abstract: To analyze the biomechanical stability of a redesigned cage, a new lateral plate and the effect of length of cage in CLIF, an L4-L5 finite element model was performed. Six different internal fixation methods were designed and operated under six conditions (Stand-alone CLIF; CLIF with unilateral pedicle screws (CLIF + UPS); CLIF with bilateral pedicle screws (CLIF + BPS); CLIF with lateral plate (CLIF + LP); CLIF with lateral plate and unilateral pedicle screws (CLIF + LP + UPS); CLIF with lateral plate and bilateral pedicle screws (CLIF + LP + BPS)). Ranges of motion (ROM) and stress distribution were evaluated. The effect of the length of cage was analyzed. The ROMs of stand-alone CLIF group and other internal fixation groups were decreased by >90% compared with the intact group. The CLIF + LP + BPS group has the minimum ROM. The CLIF + LP group has smaller ROM than stand-alone group. The stand-alone group has the minimum stress except for extension condition. The CLIF + LP model has less ROM, but a greater stress load was observed in the lateral plate. As for the length of cage, the largest stress is located at the junction between cage and distal end plate, especially in the epiphyseal ring and cortical compact. We conduct a new 'cylinder wall theory' that the cage should be placed to cover the epiphyseal ring. We recommend the length of cage should cover the epiphyseal ring to reduce the subsidence of cage.